2018
DOI: 10.1086/697575
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Manipulation of Vector Host Choice

Abstract: The transmission of many animal and plant diseases relies on the behavior of arthropod vectors. In particular, the specific preference for infected or uninfected hosts observed in many vector species is expected to affect the circulation of vector-borne diseases. Here I develop a theoretical framework to study the epidemiology and evolution of the manipulation of host choice behavior of vectors. I show that vector preference strategies have dramatic epidemiological consequences. I also explore the evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 69 publications
0
36
0
Order By: Relevance
“…These pathogens, which include viruses, bacteria, and fungi, often depend on insect herbivores as vectors for their transfer from infected to healthy, uninfected plants (Eigenbrode et al, 2018). Consequently, the epidemiology of these pathogens can be strongly influenced by the host selection and feeding behaviors of vector insects, which, in turn, are influenced by the levels of primary and secondary metabolites in plants (Gandon, 2018). Over the past two decades, many studies have demonstrated the ability of pathogens to affect vector behavior by altering features of host-plant chemistry (Stafford et al, 2011;Ingwell et al, 2012;Mauck et al, 2012;Eigenbrode and Bosque-Pérez, 2016;Mauck, 2016), including plant defense signals (Zhang et al, 2016;Carr et al, 2018), volatile emissions (Eigenbrode et al, 2002;Jiménez-Martínez et al, 2004;Mauck et al, 2010) and nutrition (e.g., leaf and/or phloem amino acid content) (Blua et al, 1994;McMenemy et al, 2012;Mauck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These pathogens, which include viruses, bacteria, and fungi, often depend on insect herbivores as vectors for their transfer from infected to healthy, uninfected plants (Eigenbrode et al, 2018). Consequently, the epidemiology of these pathogens can be strongly influenced by the host selection and feeding behaviors of vector insects, which, in turn, are influenced by the levels of primary and secondary metabolites in plants (Gandon, 2018). Over the past two decades, many studies have demonstrated the ability of pathogens to affect vector behavior by altering features of host-plant chemistry (Stafford et al, 2011;Ingwell et al, 2012;Mauck et al, 2012;Eigenbrode and Bosque-Pérez, 2016;Mauck, 2016), including plant defense signals (Zhang et al, 2016;Carr et al, 2018), volatile emissions (Eigenbrode et al, 2002;Jiménez-Martínez et al, 2004;Mauck et al, 2010) and nutrition (e.g., leaf and/or phloem amino acid content) (Blua et al, 1994;McMenemy et al, 2012;Mauck et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…He demonstrated that increasing the preference of vectors for infected hosts leads to an easier maintenance of a stable infection, compared to the model where vectors feed on their host in a random manner. Subsequent studies confirmed this result and showed that the preference of vectors for infected hosts can strongly reinforce the transmission of the parasite at the beginning of the epidemic (McElhany et al, 1995;Hosack et al, 2008;Sisterson, 2008;Chamchod and Britton, 2011;Zeilinger and Daugherty, 2014;Gandon, 2018). Parasite that are able to manipulate their vertebrate hosts to make them more attractive to vectors should be therefore favored by natural selection.…”
Section: Integration Of Vector Feeding Bias In Epidemiological Modelsmentioning
confidence: 87%
“…Parasite that are able to manipulate their vertebrate hosts to make them more attractive to vectors should be therefore favored by natural selection. However, an extreme preference of vectors for infected hosts may also limit or stop the transmission of parasites (Kingsolver, 1987;McElhany et al, 1995;Sisterson, 2008;Zeilinger and Daugherty, 2014;Gandon, 2018). Indeed, when levels of host infection in a population are very high, vector feeding bias results in most of the bites occurring on already infected hosts.…”
Section: Integration Of Vector Feeding Bias In Epidemiological Modelsmentioning
confidence: 99%
“…Note that virus modifications may also alter insect preference with respect to feeding retention of infected insects for healthy plants, and of uninfected insects for infected plants. Such traits, which can involve pathogen modification of the insect vector, are not our focus here, and have been discussed elsewhere [17,18]. Nevertheless, for completeness, see electronic supplementary material, appendix S2 for an outline of how this form of modification can be incorporated in our framework and for an explanation of why such traits are not associated with pathogen-mediated insect superabundance.…”
Section: Vector Dynamicsmentioning
confidence: 99%